Análisis ergonómico en el trabajo de mantenimiento eléctrico - Cedeño Sánchez, Carlos Xavier (2010)
This work has been carried out focusing it as a reality, social, occupational, such as ergonomics in electrical maintenance, today´s figures are alarming accidents and many of them could be avoided by applying the basic principles of ergonomics. Adequate lighting, further standards and specifications provided by manufacturers, know the positions suitable job, use the materials and instruments so as not to affect general health status of electrical professional will therefore elemental to our work. Ergonomics teaches basic principles of work and protection to for the human being so that not only managed to avoid injury or long-term consequences on health, but also improved the quality or the electrical work.